Perbedaan Keterampilan Proses Sains Siswa Kelas VIII pada Penggunaan Laboratorium Riil dengan Laboratorium Virtual Di SMP Negeri 1 Candi - Faridhotul Khoiriroh; Noly Shofiyah (International Consortium of Education and Culture Research Studies, 2019)
This study aimed to analyze the differences between students' science process skill in real laboratory and virtual laboratory at SMP Negeri 1 Candi, Sidoarjo. This study was quantitative research with a quasi-experimental design that was conducted at SMP Negeri 1 Candi. The population of this study was 321 students. The sample was selected by purposive sampling considering the equality of ability in the practicum. The Data was collected by using pre-test and post-test. The result revealed that the Fvalue 3,34 < Ftable 3,98 and significant value 0,07 > 0,05, which means there is no difference between student' science process skills in real laboratory and virtual laboratories in SMP Negeri 1 Candi.